Synthesis, characterization and computational investigation of novel metalloporphyrazines containing 15-membered O2S2-donor macrocyclic moieties - Baygu, Yasemin; Yildiz, Burak; Karac, Izzet; Dal, Hakan; Gok, Yasar (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
New metalloporphyrazines (MgPz, ZnPz) containing peripheral tetrasubstitutions derived from 7,8-dihydro-6H, 14H, 19H-dibenzo[bj][1,12,5,8]-dioxadithiacyclopentadecine-16,17-dicarbonitrile (6) have been synthesized by a multistep reaction sequence and characterized. Compound 6 has been prepared by the reaction of 1,3-di(2-bromomethyl phenoxy) propane (3) or 1,3-di(2-iodomethylphenoxy) propane (4) which were prepared via bromination or iodination of {2-[3-(2-hydroxymethylphenoxy) propoxy]-phenyl} methanol (2) and cis-1,2-dicyano-1,2-ethylenedithiolate (5). The novel magnesium porphyrazine was prepared by the cyclotetramerization reaction of 6 with magnesium butoxide. The one-step synthesis of porphyrazinato zinc complex has been achieved without a reaction sequence by using dicyano compound (6) and zinc butoxide. The prediction of the geometry optimization, normal mode frequencies, H-1, C-13 NMR, UV absorption spectra, chemical shifts, electronic properties and NBO analysis of the compound were examined by using B3LYP method with a 6-31G(d, p) basis set. These novel compounds were characterized by a combination of elemental analysis, H-1, C-13 NMR, FT-IR, UV-vis and MS spectral data. An X-ray crystal structure of dicarbodinitrile compound (6) was also investigated.
Keywords: mixed-donor macrocycle; porphyrazine; template reaction; green chemistry; X-ray investigation; computational chemistry; MOLECULAR-STRUCTURE; STAR-PORPHYRAZINES; CRYSTAL-STRUCTURE; EFFICIENT METHOD; COMPLEXES; ALCOHOLS; ENERGY; PHTHALOCYANINES; DERIVATIVES; MG(HSO4)(2); Chemistry